Joint Implementation as Development Policy - The Case of Costa Rica - Michael Dutschke; Axel Michaelowa (Hamburg Institute of International Economics (HWWA), 1998)
Joint Implementation (JI) is a potentially powerful instrument of climate policy that could lead to a high amount of additional financial flows to developing countries. Nevertheless, many NGOs and developing country representatives are very skeptical about JI and fear that it would not take into account development priorities and create new kinds of dependence on industrial countries. Therefore, developing countries and industrial countries found a compromise at the Berlin Conference of the Parties as they instituted a pilot phase for JI lasting until 2000 which does not allow crediting of reduction achieved via JI. The paper discusses first results of the JI pilot phase in Costa Rica which could be important for the evaluation of the whole pilot phase. This country has a relatively high level of economic and social development and a well-developed environmental policy which is comparable to that of advanced industrial countries. It is a major destination for ecotourism. Nevertheless, it suffers from high deforestation due to unequal distribution of land, migration and cattle ranching as well as plantation expansion. Moreover, transport emissions are rising rapidly and fossil fuel electricity generation is growing despite a target of phasing out fossil fuels completely. Costa Rica's knowledge base is high and capacity building almost not necessary. Thus, Costa Rica was able to develop creative environment policy instruments such as debtfornature swaps and biodiversity prospecting to attract foreign funding. It is not surprising that it was the first developing country to open a JI office, develop project approval criteria and host JI pilot projects. The framework for JI in Costa Rica can therefore be described as ideal compared to the average developing country. Nor is it surprising that more than half of the approved pilot projects in developing countries are situated in Costa Rica. Nevertheless, the success can at best described as mixed. Only a third of the projects are actually funded though several of them seem to be profitable even without a value for carbon. Most of them are proposed by US entities. To attract more funding, the JI office now certifies tradable carbon certificates and en-courages multi-sector large-scale projects where transaction costs are lower and coherence with national development objectives can be more easily checked. It directs its attention to public JI investors such as the Norwegian government. The renewable energy projects suffer from the unrealistic target to phase out fossil fuels by 2001 thus making JI projects in this sector impossible from that time. Therefore the bulk of projects concern forestry which is prone to uncertainties in calculation of emission sequestration. A comparison of the estimates shows wildly differing assumptions in baselines and sequestration capacity of the forests. Whether actual project implementation conforms to the plans remains to be seen. An independent verification of project results is being undertaken. The analysis of the Costa Rica case shows that JI can be only successful in the long run if the industrial countries offer incentives for investors and if baseline determination rests on a clear set of guidelines. Human and technical capacities are necessary but not sufficient conditions for successful JI in developing countries. They seem to be able to prevent complete project failures, though and can lead to innovative approaches. The issue will only be settled if large-scale JI investment is forthcoming under a regime of legally binding emission targets for industrial countries. Then the ability to process huge number of project proposals and check whether they conform to development priorities as well as monitoring and verification becomes crucial.
Keywords: 330; Entwicklungsprojekt; Klimaschutz; Umweltabkommen; Internationaler Transfer; Costa Rica